Understanding the Methodological Issues and Solutions in the Research Design of Stroke Caregiving Technology - Lobo, Elton H.; Frølich, Anne; Rasmussen, Lene J.; Livingston, Patricia M.; Grundy, John; Abdelrazek, Mohamed; Kensing, Finn (Frontiers in Public Health, 2021)
The rise in the number of cases of stroke has resulted in a significant burden on the healthcare system. As a result, the majority of care for the person living with stroke occurs within the community, resulting in caregivers being a central and challenged agent in care. To better support caregivers during the recovery trajectory poststroke, we investigated the role of health technologies to promote education and offer various kinds of support. However, the introduction of any new technology comes with challenges due to the growing need for more user-centric systems. The integration of user-centric systems in stroke caregiving has the potential to ensure long-term acceptance, success, and engagement with the technology, thereby ensuring better care for the person living with stroke. We first briefly characterize the affordances of available technologies for stroke caregiving. We then discuss key methodological issues related to the acceptance to such technologies. Finally, we suggest user-centered design strategies for mitigating such challenges.